Trabalho e desemprego nas campanhas da fraternidade da Igreja Católica no Brasil: uma análise da campanha de 1978, “Fraternidade no Mundo do Trabalho - Flores, Victor Ernesto Ochoa (2016)
This study aimed to investigate the Campanhas da Fraternidade where the speech of Catholic Church in Brazil is expressed on the issue of labor, knowing that the CF is a communication tool that generates juncture between the faithful ones and the Catholic hierarchy. Understanding and studying the speech promulgated within the CFs that express the position of the Church regarding the issue of labor and unemployment through the CF of 1978, which addressed the theme as "Fraternity in the world of labor", presents the reality of the relationship between Church, State and world of labor. This CF presents the labor reality that operated at the time of the military regime and the positioning of the Catholic Church, which through this CF, presents in an ambiguous way. Our hypothesis break part from the traditional relations between Church and State, which come out from collaborative relationships and influences, to keep itself in the public scene. This new Church procession is due to participation of Catholic bases inserted in the realities of injustice, and that will lead the episcopate to insert through social projects at the beginning of the 20th century, through the BC entered into development projects in partnership with the State. The Church misses, in the shadow of the State, in accordance with the new political circumstances, and has chosen to be close of the large masses and is positioned critically before the Military State, which in this case is unpopular and repressive, entering in the social realities through a speech of politico-religious slant. This process is originated from the historical context where the genesis of what led to the creation of CF and how the Church uses the CF as pastoral strategy to transmit his teachings to the faithful ones, to the extent that updates through the Council documents and of the Latin American episcopate, and thus adapt the requirements of the fast changing society. It is the CF of 1978 which features changes and intention between the Catholic Church and State relations regarding the issue would operate from the period of military dictatorship